Perceptions and Participation of Visually Impaired Students in the Use of an AI-Based Braille Dictionary Equipped with Audio in English Language Learning - Tulus Tulus; Urai Salam; Venny Karolina; Aunurrahman Aunurrahman; Halida Halida (Jurnal Pendidikan Terapan, 2026)
Purpose this study was motivated by the limitations of English learning for visually impaired students, which is still dominated by the use of conventional Braille without audio support, resulting in less optimal understanding of pronunciation, vocabulary, and language context. The study aims to describe students’ perceptions, analyze the role of an AI-based Braille–audio dictionary in understanding abstract materials, illustrate active participation, and identify learning obstacles and experiences. Methods this research employed a qualitative approach with a phenomenological method. Data were collected through participatory observation, in-depth interviews, and documentation studies conducted at SLB Negeri Mempawah and SLB Negeri Rasau Jaya. Findings the findings revealed that the integration of Braille and audio improved students’ understanding of vocabulary, pronunciation, and language context more comprehensively. The media also encouraged emotional engagement, active participation, and learning independence. Although technical obstacles and the need to adjust the audio pace were identified, the AI-based Braille–audio dictionary remained effective and relevant in supporting inclusive learning. Research Implications the study suggests that integrating AI-assisted Braille–audio learning media can enhance accessibility and learning outcomes for visually impaired students. The findings provide practical implications for educators, schools, and policymakers in developing more inclusive English language learning environments that support student participation, autonomy, and meaningful learning experiences. Originality this study offers a novel contribution by examining the use of an AI-based Braille–audio dictionary as an inclusive English learning tool for visually impaired students. Unlike conventional Braille-based learning resources, this approach combines tactile and auditory modalities, providing a more comprehensive learning experience that supports vocabulary acquisition, pronunciation development, and contextual language understanding.